2018
DOI: 10.1002/iub.1970
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of serum miR‐20b, miR‐17‐3p, HOTAIR, and MALAT1 in diabetic retinopathy

Abstract: Noncoding RNAs are emerging biomarkers for many diseases including diabetic retinopathy (DR). This study aimed to measure the expression levels of serum miR‐20b, miR‐17‐3p, HOTAIR, and MALAT1 in DR patients. A total of 80 patients diagnosed as type 2 diabetes (T2D) and 81 healthy subjects were recruited in this study. T2D patients were divided into three groups: nondiabetic retinopathy (NDR) group (30 patients), nonproliferative diabetic retinopathy (NPDR) group (30 patients), and proliferative diabetic retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…Among the findings in this study, one of them indicated that miR‐20b‐3p was poorly expressed, while TXNIP was highly expressed in retinal tissues of DR rats. Similarly, Shi et al have demonstrated that the expression level of miR‐20b‐3p reduced in both urine of patients and kidney tissues from animal models with hyperoxaluria‐induced calcium oxalate deposition, and it has also been clarified that miR‐20b was decreased in serum of patients with proliferative and non‐proliferative DR in contrast to the healthy controls . The overexpression of TXNIP has also been unraveled in various human diseases.…”
Section: Discussionmentioning
confidence: 90%
“…Among the findings in this study, one of them indicated that miR‐20b‐3p was poorly expressed, while TXNIP was highly expressed in retinal tissues of DR rats. Similarly, Shi et al have demonstrated that the expression level of miR‐20b‐3p reduced in both urine of patients and kidney tissues from animal models with hyperoxaluria‐induced calcium oxalate deposition, and it has also been clarified that miR‐20b was decreased in serum of patients with proliferative and non‐proliferative DR in contrast to the healthy controls . The overexpression of TXNIP has also been unraveled in various human diseases.…”
Section: Discussionmentioning
confidence: 90%
“…It is speculated that miRNA regulates one third of the human genes [4]. Meanwhile, some breakthrough study in 2016 [5] demonstrated that miRNAs are also extracellular, being present in a cell-free circulating form in the serum, plasma, saliva, tears, aqueous and vitreous humor, and urine [6,7], which could be called circulating miRNAs.…”
Section: Circulating Mirnas As Biomakers In Drmentioning
confidence: 99%
“…While a significant decrease in serum miR-20b was found in diabetic patients compared to healthy subjects, a decrease in serum miR-20b and miR-17-3p was found in NPDR and PDR groups when compared with healthy subjects. A combined analysis of these noncoding RNAs with two regulators of retinal endothelial dysfunction, Homebox antisense intergenic RNA (HOTAIR) and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), was able to discriminate diabetic patients without retinopathy from healthy controls and NPDR and PDR from diabetic patients without retinopathy, suggesting that miR-20b and miR-17-3p may be used as noninvasive biomarkers for screening of DR and the early diagnosis of PDR [115].…”
Section: Mirna In Dr: Role In Oxidative Stress and Inflammatory Signamentioning
confidence: 99%